Mineralogical Assessment Regarding the Sustainability of Mortars Exposed to Sodium Sulfate Attack. (2016) - Balog, Anca-Andreea; Cobîrzan, Nicoleta; Suciu, Ramona-Crina; Moşonyi, Emilia; Aciu, Claudiu
Abstract: The paper presents the mineralogical analysis in XRD and thin sections of three types of mortars, before and after immersion in a salty solution of sodium sulphate decahydrate (Na2SO410H2O). The proposal of the study it was to identify the chemical transformation of minerals, and the degree of mortars decay after 15 cycles of immersion in salty solution. These studies highlights the role of mineralogical analysis in conservation of building materials in order to avoid their deterioration when are exposed in aggressive environment.